(untitled) (Advancements in Homeopathic Research, 2022)
In a prospective study carried out to ascertain Scope of Homoeopathy in Acute Conjunctivitis, ninety-two cases were studied. As the immunity in children is low and the susceptibility in children is higher, hence children are more frequently attacked by the Acute Conjunctivitis. Homoeopathy has vast scope for the acute conditions. And it was seen that within a week maximum cases were treated successfully. The result shows that out of ninety two cases, eighty-nine cases recovered and its percentage is 96.14% & remaining three cases have not recovered. Thus we may conclude that Homoeopathy works instantly in acute conjunctivitis of children. The efficiency of Homoeopathy in the treatment of acute conjunctivitis in children is excellent and shows high success rate of eighty-nine out of ninety-two patients responding successfully to the treatment with no sign of recurrence in near future.